Heparan Sulfate 2-O-Sulfotransferase Is Required for Triglyceride-rich Lipoprotein Clearance - Stanford, Kristin I. (American Society for Biochemistry and Molecular Biology, 2010)
Hepatic clearance of triglyceride-rich lipoproteins depends on heparan sulfate and low density lipoprotein receptors expressed on the basal membrane of hepatocytes. Binding and uptake of the lipoproteins by way of heparan sulfate depends on the degree of sulfation of the chains based on accumulation of plasma triglycerides and delayed clearance of triglyceride-rich lipoproteins in mice bearing a hepatocyte-specific alteration of N-acetylglucosamine (GlcNAc) N-deacetylase-N-sulfotransferase 1 (Ndst1) (MacArthur, J. M., Bishop, J. R., Stanford, K. I., Wang, L., Bensadoun, A., Witztum, J. L., and Esko, J. D. (2007) J. Clin. Invest. 117, 153–164). Inactivation of Ndst1 led to decreased overall sulfation of heparan sulfate due to coupling of uronyl 2-O-sulfation and glucosaminyl 6-O-sulfation to initial N-deacetylation and N-sulfation of GlcNAc residues. To determine whether lipoprotein clearance depends on 2-O-and 6-O-sulfation, we evaluated plasma triglyceride levels in mice containing loxP-flanked conditional alleles of uronyl 2-O-sulfotransferase (Hs2st(f/f)) and glucosaminyl 6-O-sulfotransferase-1 (Hs6st1(f/f)) and the bacterial Cre recombinase expressed in hepatocytes from the rat albumin (Alb) promoter. We show that Hs2st(f/f)AlbCre(+) mice accumulated plasma triglycerides and exhibited delayed clearance of intestinally derived chylomicrons and injected human very low density lipoproteins to the same extent as observed in Ndst1(f/f)AlbCre(+) mice. In contrast, Hs6st1(f/f)AlbCre(+) mice did not exhibit any changes in plasma triglycerides. Chemically modified heparins lacking N-sulfate and 2-O-sulfate groups did not block very low density lipoprotein binding and uptake in isolated hepatocytes, whereas heparin lacking 6-O-sulfate groups was as active as unaltered heparin. Our findings show that plasma lipoprotein clearance depends on specific subclasses of sulfate groups and not on overall charge of the chains.